Seasonal and Regional Differences in Extreme Rainfall Events and Their Contribution to the World’s Precipitation: GPM Observations - Shailendra Kumar; Yamina Silva; Aldo S. Moya-Álvarez; Daniel Martínez-Castro (Advances in Meteorology)
In the present study, five-year of precipitation features (PFs) datasets, based on Global Precipitation Measurement (GPM), are used to investigate the global and regional characteristics of extreme rainfall events (EREs). The EREs are defined based on the PFs area, depth (maximum height of radar reflectivity), and the rain rate and called them largest, deepest, and intense EREs, respectively. The EREs are divided into top 10%, 1%, 0.1%, and 0.01% based on their frequency of occurrences. It is observed that occurrences of EREs belonging to less than top 0.01% EREs follow the tropical rainfall climatology over the tropics based on all the parameters. Subtropical oceanic areas consist of a higher frequency of largest EREs, whereas tropical land areas consist of the higher number of deepest EREs. The most intense EREs (top 0.01%) are uniformly distributed over tropical areas and subtropical oceans, and spatial distribution shows that a deepest ERE belongs to intense EREs in the tropical land areas. Large differences between the precipitation contribution from the largest and deepest EREs are seen; for example, the top 1% of largest EREs contribute to ∼80.7% of Earth’s precipitation, whereas the corresponding percentage for deepest EREs is only 53%. On the regional and seasonal scale, South Asia (SAsia) and South America (SA) nearly show common features, as oceanic and land areas consist of largest and deepest EREs, respectively, and contribute to higher precipitation. Subtropical latitudes over South America, including Sierra de Cordoba and La Plata basin, consist of deepest and intense EREs and match with those of the Indo-Gangetic plain over South Asia, which also shows the similar characteristics. EREs based on various parameters are strongly linked over SAsia compared to SA. For example, the largest top 10% EREs have a higher probability to be part of the top 10% deepest and intense EREs over SAsia. The seasonal and regional water budget reveals different characteristics, as in the southern hemisphere, the deeper EREs contribute to the higher fraction of rainfall, but over SAsia, the shallower EREs could also contribute to significant rainfall.